2009
DOI: 10.18590/euscorpius.2009.vol2009.iss81.1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation of Mesobuthus martensii (Karsch, 1879) (Scorpiones: Buthidae) in Northern China

Abstract: Comparative statistical analysis of morphology of Mesobuthus martensii and Mesobuthus eupeus (Scorpiones: Buthidae) indicated highly significant differences between these two species. Mann-Whitney U test showed that: except Ca_L/AW, Ca_AW/PW and Met-V_L/H in female, Ca_AW/PW and Met-V_L/H in male, all morphometric ratios demonstrated significant differences between M. martensii and M. eupeus. Principal component analysis (PCA) showed that M. martensii and M. eupeus are clearly different species in morphology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Qinghai, Sichuan and Xinjiang, are also with border on of Xizang. In Qinghai, just Mesobuthus martensii martensii (Karsch, 1879) reported in its northeast (Zhu et al, 2004; Zhang & Zhu, 2009). There is no scorpion species reported in Sichuan (Zhu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qinghai, Sichuan and Xinjiang, are also with border on of Xizang. In Qinghai, just Mesobuthus martensii martensii (Karsch, 1879) reported in its northeast (Zhu et al, 2004; Zhang & Zhu, 2009). There is no scorpion species reported in Sichuan (Zhu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…All of the eight species of Chaerilus from China found in Xizang, 10 of 11 species of Scorpiops from China living in Xizang (others: Scorpiops jendeki Kovařík, 1994 found in Yunnan, one unnamed species of Scorpiops in Hubei see Di et al 2011a), 4 of 12 species of Euscorpiops from China found in Xizang (other 8 species in Yunnan; see Di et al 2011b). The scientific expedition investigation of some areas of China has been finished basically which reflected in the papers (Qi et al 2005; Shi et al 2007; Zhang and Zhu, 2009; Di et al 2009, 2010, 2011a and b, 2012; Sun and Sun, 2011). Followed these reports, Xizang is the richest area in China in scorpion diversity.…”
Section: Introductionmentioning
confidence: 99%
“…In other localities, M. martensii could have yellowish or pale yellow tergites [9]. Zhang & Zhu (2009) analyzed the intraspecific morphological differences of M. martensii from different localities in China; however, these differences were under subspecies level [10]. The results based on a few specimens with no gender information provided by Zhang & Zhu (2009) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang & Zhu (2009) analyzed the intraspecific morphological differences of M. martensii from different localities in China; however, these differences were under subspecies level [10]. The results based on a few specimens with no gender information provided by Zhang & Zhu (2009) [10]. In addition, the LD50 values of M. martensii venom from different localities in mice were different: compared with the venom of populations obtained from Henan, Liaoning and Shandong Provinces, the LD50 value of venom of the population procured from Shanxi Province in mice was the smallest [11].…”
Section: Introductionmentioning
confidence: 99%